Impacts of electric vehicle charging stations and DGs on RDS for improving voltage stability using honey badger algorithm - Thiruveedula, Madhubabu; Asokan, K.; Subrahmanyam, JBV (Institute of Advanced Engineering and Science, 2024)
The intelligent computational technique used in this research handles the multi-objective voltage stability optimization (MOVSO) problem in radial distribution systems (RDS). The objectives of the proposed research are to minimize network loss, lower the average voltage deviation index (AVDI), and improve the voltage stability index (VSI) of RDS by taking into account the recently created distributed generators (DGs) and electric vehicle charging stations (EVCSs). To address the MOVSO problem, a novel and innovative honey badger algorithm (HBA) optimization technique is put forth. The two stages of HBA, known as the